KESADARAN DAN PENJELASAN SEJARAH: Studi Kritis Surat Soekaswa Soereng Widojo Kepada Mr. Muhammad Yamin Menteri PP dan K Tertanggal 15 Februari 1955 - Suharto, Suharto (History Department, Faculty of Humanities, University of Jember, 2018)
This article explains the history of how the society consciousness existing in Java that history is basically not separated from myths. Various legends, myths, fairy tales, chronicle, saga, and tambo are typical views or perceptions of the archipelago. Even when the famous figure of Diponegoro is said to be dead, there are people who say it is impossible. This situation can not be separated because the role of Diponegoro as an important figure in the resistance against colonization in the mid-18th century that has become part of the meaning of the myth in history. This article used a psychological history approach, when one becomes part of a historical event and tries to imagine, that history is basically inseparable from belief even though reality is a real event. The conclusion of this article is that in the people's beliefs, important figures, can be physically dead, but even their spiritual teachings are alive or regarded as just kings who are able to liberate the Javanese from various pressures. Keywords: History; myth; awareness; Java